Estratégias de seleção de genótipos de soja por meio de modelos mistos e abordagens multivariadas - Andrade, Andréa Carla Bastos [UNESP] (2015)
In genetic breeding, beyond good experimental conduction, and proper data collection, the quality of statistical-genetic analysis is given by the application of methodologies that seek to enhance the selection process, through observation of the relationship between the characteristics evaluated and the achievement of values that are in accordance with reality. The aim of this study was to select soybean genotypes, in an assay in the agricultural year 2013/2014, derived from crosses between conventional and transgenic lines (Roundup Ready), using jointly the REML/BLUP approaches, analysis of factors and principal components, processed with the following characteristics: number of days to flowering (NDF), plant height at flowering (APF), number of days to maturity (NDM), plant height at maturity (APM), height of the first pod insertion (AIV ), lodging (AC), agronomic value (VA), number of branches (NB), number of nodes per plant (NN), number of pods per plant (NV), grain yield (PG) and one hundred seed weight (PCS). Three agronomic selection processes were identified to select genotypes that discriminate genotypes containing more specific properties. The process 1 (AIV, NR, NV, NN and PG) was efficient for the selection of genotypes with good yield components, earlier, smaller sizes and with lodging resistance